Sinergias y tensiones en la construcción de políticas públicas: una visión sobre la descentralización política y administrativa en Colombia (2008)
ABSTRACT: This paper presents a short analysis of the institutional, interorganizational and subjective conditions that allows or not, the articulation between organizations around policy and social development projects. I´m proposing that the concept of articulation is tied to the concept of efficiency, and only with an articulated efficiency it is possible to reach an integral and integrated development. This analysis will focuses in the fulfill of the municipal actors and their contingencies for the articulated action.